2019
DOI: 10.3390/ijerph16050840
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Soundscape Factors Influencing Perceptions of Square Dancing in Urban Streets: A Case Study in a County Level City in China

Abstract: Square dancing is a popular music-related group physical exercise for health benefits in China mainly participated by mid-aged women and elderly people. This paper investigates the soundscape and enjoyment of the square dancing in urban streets through a case study in Lichuan, a county level city in southwest China, in December 2017. It examines the impact of gender, age, participation and places on perceptions of square dancing soundscape. Two sites along two main urban streets in the city were selected to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…A longitudinal study by Weinstein (1978) showed that individual differences in college students can lead to different reactions to noise including lower academic ability, less secure social interactions, greater need for privacy. There is evidence to suggest that among all secondary factors, age and gender are considered more important potential confounders (Xiao & Hilton, 2019; Gulian & Thomas 1986).…”
Section: Individual Differences and Soundscapementioning
confidence: 99%
“…A longitudinal study by Weinstein (1978) showed that individual differences in college students can lead to different reactions to noise including lower academic ability, less secure social interactions, greater need for privacy. There is evidence to suggest that among all secondary factors, age and gender are considered more important potential confounders (Xiao & Hilton, 2019; Gulian & Thomas 1986).…”
Section: Individual Differences and Soundscapementioning
confidence: 99%
“…Steele and colleagues [14] carried out an interventional study with an unsupervised installation in a public pocket park allowing users to play audio content from personal devices over publicly provided speakers and they found out that the soundscape was experienced as more pleasant for both users and non-users, and the calmness and appropriateness of the place were not affected. Xiao and Hilton [15] investigate the factors influencing sound environments perception in relation to "square dancing", a growing social phenomenon in many Chinese cities. A better understanding of contextual factors and aspects related to the interactions between people and places is required to characterize soundscapes holistically, as pointed out by Hermida and colleagues [16] in their case studies in Lisbon and Bogotá.…”
Section: Extending the Research Scope To More Soundscape Quality Dimementioning
confidence: 99%
“…Some of the above-mentioned studies were looking into the soundscape interventions 'as they are' [42,45]. Other were trying to assess their impact by defining a baseline condition and then looking into the conditions such as 'on and off'/'with or without' [44,57], 'before and after' [1,7] or comparing different scenarios and exposure conditions [4,5,38,58]. In terms of selecting key conditions, different time frames were featured, spanning from several years between the conditions [36,44] to several minutes in the same time of day [4].…”
Section: Introductionmentioning
confidence: 99%